ICONOCLASTS AND COUNTER TERRORISM AGAINST STATE ORGANIZED TERROR: A STUDY OF PERSPECTIVES IN NIGERIAN HISTORY AND DRAMA - Ademakinwa, Adebisi; Bello, Saheed (International Review of Humanities Studies, 2023)
The paper assesses the issue of terrorism as a social reality present in the Nigerian state from its origination and the questions treated by the paper among others include: what dimensions did the occurrences of terrorism take on Nigerian socio-political sphere? What are the counter measures taken by individual and groups in dealing with state organized terrorism? What are the dimensions state organized terrorism take in the modern Nigerian state? Lekan Balogun‟s Ogun Skugga is used primarily while other literary works are used to supplement. The paper argues that the state organized terrorism was a surreptitious method of coercion adopted by the colonial authorities equally and eventually adopted by the political elites after independence. It also maintains that individual and groups engaged in subtle and overt terrorism as counter measure against state sponsored terrorism. Again, current acts of terrorism organized by state are multidimensional so also are variables presented by ethnic, tribal and political inclinations which in turn stimulate approaches by individual and groups in counter measures. The importance of this work is the perspectives it presents from history and drama to assess the issue of terrorism and its relevance to modern Nigerian society.